Meta-Analisis Implementasi Virtual Laboratorium Dalam Proses Pembelajaran Dan Sains - Sudirman Sudirman; Zaenal Abidin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The learning process related to technology and science really needs to be applied in the world of education, one of which is the Virtual Laboratory. The purpose of this study was to analyze the application of a scientific approach assisted by virtual laboratory media in the learning and science process. This study uses a meta-analysis method. The journal meta-analysis used is the result of an analysis of articles from accredited international journals through a Google search https://www.sciencedirect.com/ with categories Q1 and Q2 which have study topics related to the implementation of virtual laboratories in the learning process and science as many as 15 articles. Data analysis was carried out in a qualitative descriptive way. Based on the results of data analysis obtained that the implementation of virtual laboratories can help in the science learning process.